SUSTAINABLE WATER MANAGEMENT IN UNIVERSITIES: PERCEPTIONS, BEHAVIOURS, AND CHALLENGES - Setiani, Hastin; Sutjiningsih, Dwita; Sari, Riri Fitri (Journal of Environmental Science and Sustainable Development, 2025)
Universities are increasingly adopting the “living laboratory” model to implement and evaluate sustainability innovations. These settings enable students, staff, and stakeholders to co-create and test real-world solutions, including those related to water use. Universitas Indonesia promotes sustainability through an integrated approach encompassing policy development, academics programs, and infrastructures. Prior studies using the Theory of Planned Behavior (TPB) have demonstrated that attitudes and perceived norms significantly influence sustainable behavior. However, limited research has examined how these dynamics operate within Indonesian universities or how university-based initiatives may contribute to broader urban water management. This study addresses that gap by examining perceptions, behaviors, and challenges related to sustainability in a university, while also assessing the relevance of campus-based interventions to inform wider urban sustainability transitions. A cross-sectional, non-probability survey was conducted with 87 students and staff at the Health Sciences Cluster Building (RIK UI), Universitas Indonesia. A structured questionnaire was use to assess participants’ understanding of sustainability, perceptions of institutional performance, initiative effectiveness, course evaluations, and behavior frequency. Validity and reliability testing confirmed internal consistency. Chi-square tests were used to examine associations among variables, qualitative analysis, and multiple linear regression was used to identify behavioral predictors. Respondents identified inadequate infrastructure and ineffective communication as barriers. Despite high level of awareness, reported engagement in water-saving practices remained low. Chi-square results revealed significant associations between perception and behavior. Regression analysis revealed that sustainability understanding and perceptions of institutional performance were significant predicted of the frequency of sustainable behaviour, aligning with TPB’s attitude and subjective norm. These findings show that awareness alone is not sufficient—targeted sustainability education is needed to motivate behavior change. When embedded in university living laboratories, such education can help bridge the awareness–action gap and support scalable solutions for urban water governance.